2019
DOI: 10.1128/jb.00016-19
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of PASTA Kinase Signaling by Differential Modification

Abstract: Transmembrane Ser/Thr kinases containing extracellular PASTA (penicillin-binding protein [PBP] and Ser/Thr-associated) domains are ubiquitous among Actinobacteria and Firmicutes species. Such PASTA kinases regulate critical bacterial processes, including antibiotic resistance, cell division, cell envelope homeostasis, and virulence, and are sometimes essential for viability. Previous studies of purified PASTA kinase fragments revealed they are capable of autophosphorylation in vitro, typically at multiple site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…No specific site on the activation loop was obviously more important than any other, and the effect of phosphorylation at multiple sites appeared to be additive (Labbe et al, 2019).…”
Section: Irek Architec Turementioning
confidence: 98%
See 2 more Smart Citations
“…No specific site on the activation loop was obviously more important than any other, and the effect of phosphorylation at multiple sites appeared to be additive (Labbe et al, 2019).…”
Section: Irek Architec Turementioning
confidence: 98%
“…However, it remains unclear how, or if, that interaction modulates the activity of FhaA or the PASTA kinase itself. Labbe et al (2019) identified 2 sites of phosphorylation on the juxtamembrane linker of IreK (Labbe et al, 2019). Mutations The cytoplasmic kinase domains of PASTA kinases are the most highly conserved domains and belong to the superfamily of Hanks-type kinases that are widespread in eukaryotic organisms.…”
Section: Irek Architec Turementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that antibiotic resistance can be driven by bacterial kinases. Particularly, transmembrane Hanks kinases with PASTA domains are seen to confer resistance to cell-wall-inhibiting b-lactam-type antibiotics in various Gram-positive species [14,19,34,36,[218][219][220][221]. Although this may not be surprising given their role in cell division and cell wall homeostasis as described earlier, the mechanism(s) by which Hanks-type PASTA kinases promote b-lactam resistance are only poorly defined.…”
Section: Phosphorylation In Antibiotic Resistancementioning
confidence: 99%
“…Deleting PhpP augments StkP phosphorylation levels and confers drug resistance, suggesting that StkP inactivation could be a strategy for overcoming S. pneumoniae blactam resistance [218]. Similarly, L. monocytogenes PrkA, Enterococcus faecalis IreK, C. difficile PrkC, and MRSA Stk1 are all required for resistance to different types of b-lactams [19,34,36,[219][220][221]. In S. aureus, b-lactams induce the phosphorylation of the blactam antibiotic-sensing protein BlaR1 and this initiates a cascade leading to expression of antibiotic resistance determinants [223].…”
Section: Phosphorylation In Antibiotic Resistancementioning
confidence: 99%